Too hot to play it cool? Temperature and media bias - David Stadelmann; Tobias Thomas; Nikita Zakharov (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2023)
This paper examines the impact of outdoor temperature on media bias. We use 12 years of daily hand-coded data on the tonality of news broadcast by the three major US news networks, ABC News, CBS News, and NBC News, all headquartered in New York City, and merge it with granular, geospatial weather data. Our identification strategy exploits detailed variations in local daily high temperatures to estimate the effect of heat on media bias in news reporting about the Republican and Democratic parties, controlling for time and network-month fixed effects. We find a positive effect of a substantial magnitude: a 1êC increment in daily maximum temperature on a hot day (>25êC) leads to a 20% increase in the media bias measured as the difference in the share of negative news about the Republicans and the Democrats. This effect exists only for maximum temperatures, as opposed to minimum or average temperatures. The results are robust to placebo tests using past or future temperatures. Our findings extend the previously established link - from hot temperatures to negative affect and a decline in cognitive ability - to the determinants of media bias.
Keywords: L8; D7; 330; media bias; tonality; temperature; U.S. newscasts